High hydrostatic pressure‐assisted extraction of lipids from Lipomyces starkeyi biomass. Issue 11 (3rd October 2022) - Tuhanioglu, Arda; Alpas, Hami; Cekmecelioglu, Deniz
Abstract : Abstract: The purpose of this study is to evaluate the effect of high hydrostatic pressure (HHP) as a novel approach for yeast cell disruption and lipid extraction from Lipomyces starkeyi DSM 70295 grown in glucose medium (40 g/L and C/N:55/1) at initial pH of 5.0, 25°C, and 130 rpm for 8 days. HHP extraction conditions including pressure, time, and temperature were optimized by response surface methodology. The high speed homogenizer‐assisted extraction (HSH) was also used for comparison. The biomass subjected to HHP was examined under scanning electron microscopy and light microscope. A maximal lipid yield of 45.8 ± 2.1% in dry cell basis (w/w) was achieved at 200 MPa, 40°C, and 15 min, while a minimum yield of 15.2 ± 0.9% was observed at 300 MPa, 40°C, and 10 min ( p  < 0.05). The lipid yield decreased with increasing pressure. It was demonstrated that low pressure (200 MPa) collapsed the cells, while high pressure (400 MPa) created protrusions on the cell wall and cell fragments spread in the environment. This study favors HHP as a promising method for Lipomyces oil extraction. Practical Application: Single‐cell oils are considered future alternatives to plant‐based oils as food additives and dietary supplements. Oleaginous microorganisms accumulate oils in their cell plasma, which makes extraction essential. One of the main obstacles with existing methods is the utilization of strong acids to destroy cell walls. This study aims to demonstrate high hydrostatic pressure as a rapid method for lipid extraction from oleaginous yeast Lipomyces starkeyi .